2016
DOI: 10.1075/ihll.6.01col
|View full text |Cite
|
Sign up to set email alerts
|

Task-related effects in the prosody of Spanish heritage speakers and long-term immigrants

Abstract: We compare the extent to which Spanish heritage speakers and long-term immigrants in the United States differ in their intonation of broad focus declaratives, and propose that the between-group variability is motivated by the specific language learning/literacy conditions of each group. Results from a phonetically balanced reading task and an elicited narrative revealed significant differences between the two groups in their realization of pitch accents in read speech but not in the narratives. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…While Benmamoun et al (2013, p. 140) observed that research on HSs' phonology has "barely scratched the surface", numerous publications on adult bilingual HSs have since been published (on segmental properties, see, e.g., Amengual 2012Amengual , 2016Nagy and Kochetov 2013;Mayr and Siddika 2018;Elias et al 2017;Kissling 2018;Einfeldt et al 2019; on supra-segmental properties, see, e.g., Chang et al 2011;Colantoni et al 2016;Henriksen 2016;Kim 2019Kim , 2020. Studies on global 1 accent that have looked at both native languages of adult HSs have shown that HSs are most often perceived as foreign speakers when speaking their HL but as native when speaking their ML (Kupisch et al 2014(Kupisch et al , 2020Lloyd-Smith et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While Benmamoun et al (2013, p. 140) observed that research on HSs' phonology has "barely scratched the surface", numerous publications on adult bilingual HSs have since been published (on segmental properties, see, e.g., Amengual 2012Amengual , 2016Nagy and Kochetov 2013;Mayr and Siddika 2018;Elias et al 2017;Kissling 2018;Einfeldt et al 2019; on supra-segmental properties, see, e.g., Chang et al 2011;Colantoni et al 2016;Henriksen 2016;Kim 2019Kim , 2020. Studies on global 1 accent that have looked at both native languages of adult HSs have shown that HSs are most often perceived as foreign speakers when speaking their HL but as native when speaking their ML (Kupisch et al 2014(Kupisch et al , 2020Lloyd-Smith et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Einfeldt et al (2019) found that heritage speakers of Italian maintain the contrast between singleton and geminate consonants. However, in other areas they show variability that is different from monolingual norms (Alvord & Rogers, 2014;Amengual, 2016;Colantoni et al, 2016;Godson, 2004;Henriksen, 2015;Robles-Puente, 2014;Ronquest, 2012Ronquest, , 2013. Studies have found that heritage language vowel space either shows assimilation to or dissimilation from that of the majority language (Cummings Ruiz, 2019;Ronquest, 2012Ronquest, , 2013 and that heritage language stop productions are affected by factors such as cognate status (Amengual, 2012), code-switching (Łyskawa, Maddeaux, Melara & Nagy, 2016), and speaker generation (Mayr & Siddika, 2018;Nodari, Celata & Nagy, 2019).…”
Section: Understanding Heritage Phonological Grammarsmentioning
confidence: 89%
“…Compared to this, less research has been done in phonological domains, most likely given that positive effects of early exposure have been attested on heritage language pronunciation (Au, Knightly, Jun & Oh, 2002;Knightly, Jun, Oh & Au, 2003). Nevertheless, recent studies on heritage language phonology discuss the existence of a "heritage accent" (Au, Oh, Knightly, Jun & Romo, 2008;Lloyd-Smith, Einfeldt & Kupisch, 2020;Stangen, Kupisch, Proietti Ergün & Zielke, 2015) and found deviations from monolingual norms at both segmental (Amengual, 2012(Amengual, , 2016Elias, McKinnon & Milla-Muñoz, 2017;Godson, 2004;Kissling, 2018;Ronquest, 2013;Willis, 2005) and suprasegmental levels (Chang, Yao, Haynes & Rhodes, 2011;Colantoni, Cuza & Mazzaro, 2016;Henriksen, 2016;Kim, 2019;Kim, 2020). For instance, Au et al (2008) found that Spanish heritage speakers, regardless of whether they regularly used Spanish during childhood, sounded more native-like than late L2 learners, but when compared with non-heritage native speakers, their speech was perceived to have a stronger foreign accent.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, it was assumed that HSS' phonology matched that of monolinguals. A growing body of research, however, shows quantifiable differences between bilingual and monolingual speakers in various aspects of pronunciation (Amengual, 2012;Colantoni, Cuza, & Mazzaro, 2016;Knightly, Jun, & Au 2003;Rao, 2015;Robles-Puente, 2014; among others). These differences seem to be largely the result of transfer from the dominant second language onto the heritage language.…”
Section: Literature Reviewmentioning
confidence: 99%